DISKRIMINASI TERHADAP NILAI FEMINIMISME DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER - Teguh Alfaidzin; Ida Ayu Made Wedasuwari; I Gusti Ayu Putu Tuti Indrawati (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2021)
The purpose of this research is: (1) to find out the forms of discrimination and (2) to know the value of feminism in the novel "Earth Man" by Pramoedya Ananta Toer. This type of research uses a qualitative descriptive approach by descriptive writing. Data collection method is done using documentation and literature method, namely tracing data from books and online media so that researchers can find information data online as quickly and easily as possible and can be accounted for academically. While the steps to analyze the data i.e. (1) reduce the data (2) present the data (3) verifiation and conclude the data. The results show that (1) basically, the author raises injustice through the form of discrimination experienced by women in this novel. One way is to describe the violation of the rights and discredit of their existence. Through "Earth Man", the author wants to remind us that everyone has equal rights and others must respect those rights regardless of their status, position, ethnicity, nation, or gender. The author finds forms of discrimination in the novel "Earth Man" namely: (a) discrimination in the family, (b) discrimination in society, (c) discrimination in law and politics, (d) discrimination in religion, and (d) discrimination in the economy. Writers who oppose discrimination, including discrimination against women, found a struggle against all forms of discrimination, especially reflected by two figures, Nyai Ontosoroh and Annelies Mellema. Through this figure the author discovers the values of feminism contained in the novel "Earth Man" namely (a) liberal feminism, (b) socialist feminism and (c) multicultural feminism.